Pleiotropic genetic effects influencing sleep and neurological disorders - Veatch, Olivia J (Lancet Neurol, 2017)
Research evidence increasingly points to the large impact of sleep disturbances on public health. Many aspects of sleep are heritable and genes influencing traits such as timing, EEG characteristics, sleep duration, and response to sleep loss have been identified. Notably, large-scale genome-wide analyses have implicated numerous genes with small effects on sleep timing. Additionally, there has been considerable progress in the identification of genes influencing risk for some neurological sleep disorders. For restless legs syndrome, implicated variants are typically in genes associated with neuronal development. By contrast, genes conferring risk for narcolepsy function in the immune system. Many genetic variants associated with sleep disorders are also implicated in neurological disorders in which sleep abnormalities are common; for example, variation in genes involved in synaptic homoeostasis are implicated in autism spectrum disorder and sleep-wake control. Further investigation into pleiotropic roles of genes influencing both sleep and neurological disorders could lead to new treatment strategies for a variety of sleep disturbances.